The örebro Musculoskeletal Screening Questionnaire: Validation of a modified primary care musculoskeletal screening tool in an acute work injured population - Gabel, C.; Melloh, Markus; Burkett, B.; Osborne, J.; Yelland, M. (2012)
The original örebro Musculoskeletal Pain Questionnaire (original-öMPQ) was developed to identify patients at risk of developing persistent back pain problems and is also advocated for musculoskeletal work injured populations. It is critiqued for its informal non-clinimetric development process and narrow focus. A modified version, the örebro Musculoskeletal Screening Questionnaire (öMSQ), evolved and progressed the original-öMPQ to broaden application and improve practicality. This study evaluated and validated the öMSQ clinimetric characteristics and predictive ability through a single-stage prospective observational cohort of 143 acute musculoskeletal injured workers from ten Australian physiotherapy clinics. Baseline-öMSQ scores were concurrently recorded with functional status and problem severity outcomes, then compared at six months along with absenteeism, costs and recovery time to 80% of pre-injury functional status. The öMSQ demonstrated face and content validity with high reliability (ICC2.1 = 0.978, p < 0.001). The score range was broad (40-174 öMSQ-points) with normalised distribution. Factor analysis revealed a six-factor model with internal consistency a = 0.82 (construct range a = 0.26-0.83). Practical characteristics included completion and scoring times (7.5 min), missing responses (5.6%) and Flesch-Kincaid readability (sixth-grade and 70% reading-ease). Predictive ability öMSQ-points cut-off scores were: 114 for absenteeism, functional impairment, problem severity and high cost; 83 for no-absenteeism; and 95 for low cost. Baseline-öMSQ scores correlated strongly with recovery time to 80% functional status (r = 0.73, p < 0.01). The öMSQ was validated prospectively in an acute work-injured musculoskeletal population. The öMSQ cut-off scores retain the predictive capacity intent of the original-öMPQ and provide clinicians and insurers with identification of patients with potentially high and low risks of unfavourable outcomes. © 2012 Elsevier Ltd.